Clothes for work, play & display - Morley, Jacqueline; Salariya, David (London F. Watts, 1992)
Traces the development of clothing from prehistoric times to future possibilities, describing adaptations brought about by social, political, and technological changes.
Includes index.
Keywords: Costume -- History -- Juvenile literature; Clothing and dress -- History -- Juvenile literature; Clothing and dress -- History; Costume -- History